TEACHING ENGLISH TO YOUNG LEARNERS - Yunusova Sojida Mamadaliyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article provides information on ways to teach English to young learners.